2018
DOI: 10.3390/toxins10050204
|View full text |Cite
|
Sign up to set email alerts
|

Distal Colon Motor Dysfunction in Mice with Chronic Kidney Disease: Putative Role of Uremic Toxins

Abstract: Although gastrointestinal complications are a common feature of patients with chronic kidney disease (CKD), the impact of uremia on bowel motility remains poorly understood. The present study was, therefore, designed to investigate the impact of uremia on gut motility. Kidney failure was induced in mice by chemical nephrectomy using an adenine diet (0.25% w/w). Gastrointestinal transit time and colon motility were explored in vivo and ex vivo. Colons from control mice were incubated with uremic plasma or uremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…A recent experimental study by Hoibian et al suggested a mechanism that links CKD-related gut dysbiosis to constipation [16]. In this study, adenine-induced CKD mice showed a 1.8-fold longer gastrointestinal transit time than the control mice.…”
Section: Gut Dysbiosissupporting
confidence: 54%
See 1 more Smart Citation
“…A recent experimental study by Hoibian et al suggested a mechanism that links CKD-related gut dysbiosis to constipation [16]. In this study, adenine-induced CKD mice showed a 1.8-fold longer gastrointestinal transit time than the control mice.…”
Section: Gut Dysbiosissupporting
confidence: 54%
“…Wu et al reported that the colonic transit time of patients treated with hemodialysis (HD) or peritoneal dialysis (PD) was significantly longer than that of age and sex-matched healthy subjects [15]. Delayed intestinal transit was also observed in CKD animal models [16][17][18]. Thus, constipation in CKD may primarily be classified as the slow transit type.…”
Section: Prevalence Of Constipation In Ckdmentioning
confidence: 99%
“…In addition, decreased gastrointestinal motility has been linked directly to uremia by causing dysbiosis and colonic inflammation secondary to increased uremic toxin exposure in rodent models . In an ex vivo rodent model, incubation of colons with the gut‐derived uremic toxins IS and pCS, but not urea, was shown to decrease force of contraction by 66% and 55%, respectively . This finding supports the idea that uremia directly causes impaired colonic motility, although other factors such as dehydration and hypokalemia also may be factors.…”
Section: Discussionsupporting
confidence: 61%
“…For example, isovaleric acid has been shown to cause colonic smooth muscle relaxation in an ex vivo rodent model . In addition, decreased gastrointestinal motility has been linked directly to uremia by causing dysbiosis and colonic inflammation secondary to increased uremic toxin exposure in rodent models . In an ex vivo rodent model, incubation of colons with the gut‐derived uremic toxins IS and pCS, but not urea, was shown to decrease force of contraction by 66% and 55%, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…With a few notable exceptions, the strict dietary restrictions (e.g., low-fiber diets [to avoid hyperkalemia] and limited fluid intake [to avoid volume overload]), frequent use of constipation-inducing medications (e.g., phosphate binders, potassiumlowering agents, calcium channel blockers, opioids, iron supplements, and antidepressants), uremic toxins, and altered gut microbiota, all of which are typically present in patients with CKD, may further contribute to increase the prevalence of constipation in this particular population. 6, [77][78][79] The greater reported prevalence of constipation in patients on HD (vs. PD) may be attributable to their stricter dietary restriction, longer physical restraint during dialysis treatment (and potential resultant stool withholding), and/or more rapid and greater volume removal (ultrafiltration). 6 Constipation and Gut Microbiota in CKD Over the past few decades, the characteristics and functions of gut microbiota have been extensively studied, and emerging evidence has revealed the biological links of altered gut microbiota (i.e., gut dysbiosis) with both constipation and CKD.…”
Section: Pathophysiology and Etiology Of Constipation In Ckdmentioning
confidence: 99%